Procedure Time for Gastric Endoscopic Submucosal Dissection according to Location, considering Both Mucosal Circumferential Incision and Submucosal Dissection - Hironori Konuma; Kenshi Matsumoto; Hiroya Ueyama; Hiroyuki Komori; Yoichi Akazawa; Misuzu Ueyama; Yuta Nakagawa; Takashi Morimoto; Tsutomu Takeda; Kohei Matsumoto; Daisuke Asaoka; Mariko Hojo; et al. (Gastroenterology Research and Practice)
Background. Previous assessments of technical difficulty and procedure time for endoscopic submucosal dissection (ESD) of gastric neoplasms did not take into account several critical determinants of these parameters. However, two key phases of ESD determine the total procedure time: the mucosal circumference incision speed (CIS) and submucosal dissection speed (SDS). Methods. We included 302 cases of en bloc and R0 resection of gastric neoplasms performed by 10 operators who had completed the training program at our hospital. Twelve locations were classified based on multiple criteria, such as condition of surrounding mucosa, lesion vascularity, presence of submucosal fat, ulcers, scars, fibrosis, and scope and device maneuverability. Lesions in different locations were classified into three groups based on the length of the procedure: fast, moderate, or late. Results. A significant difference was found in CIS and SDS for each location (p<0.01), which demonstrates the validity of this classification system. In several locations, CIS and SDS were not consistent with each other. Conclusion. CIS and SDS did not correspond to each other even for lesions in the same location. Consideration of ESD procedure time for gastric neoplasms requires a more elaborate classification system than that previously reported.